Experimental study and steady-state model of a novel plate loop heat pipe without compensation chamber for CPU cooling. (February 2020) - Du, Sheng; Zhang, Quan; Hou, Peilin; Yue, Chang; Zou, Sikai
Highlights: A new structure loop heat pipe without compensation chamber was designed and tested. Liquid line wick can impede heat leakage and vapor permeation. Liquid line wick is beneficial for startup process and steady operation of LHP. Mathematical model to predict operating temperature of LHP has a good accuracy. Abstract: In this study, a new type of loop heat pipe (LHP) without compensation chamber is designed and manufactured, meanwhile the liquid line is fitted with a sintered wick to enhance startup and steady operation capacity. Specifically, the thermal characteristics of the LHP are studied experimentally. The results show that the LHP can start up smoothly at any heat load and the highest temperature of LHP does not exceed 90 °C. The fluid at the liquid line is subcooled, which is beneficial for the startup and steady operation of LHP. When the heat load is in range of 10 W to 50 W, the LHP works at variable conductance mode, and the system thermal resistance and the loop thermal resistance both decrease sharply with the increasing heat load. When the heat load is in range of 50 W to 150 W, the LHP enters a constant conductance mode, and the system thermal resistance and the loop thermal resistance remain basically constant. Besides, the steady-state model of LHP used to predict the operating temperature of LHP is established. The simulation results were compared with the experimental data, and the maximum relative error of evaporator, vapor, condenser outlet and liquid line wick inlet temperature are less than 15%.